29th Annual Meeting of the American Society for Reproductive Immunology. (September 2009) - Daher, Silvia; Sharma, Surendra
The 29th Annual Meeting of the American Society for Reproductive Immunology was held on 5–9 June 2009, in Orlando (FL, USA). Peter Hansen and Mary Brown co-chaired the conference. The co-chairs and a scientific committee put together an outstanding program that included the most contemporary topics in reproductive immunology, with special focus on intrauterine infections and reproductive anomalies. A highlight of the meeting was the pre-meeting postgraduate course, which was attended by a large group of young investigators and trainees. The participants in the postgraduate course and the main meeting represented an international milieu of investigators, students and health professionals.